Marketing strategy analysis in increasing customer buying interest at Sun Café Gunungsitoli city - Rostina Zendrato; Emanuel Zebua (Enrichment : Journal of Management, 2023)
The purposes of this study to find out and analyze marketing strategies to increase customer buying interest at Sun Café, Gunungsitoli City. The type of research used in this research is field research, using a qualitative approach. Descriptive data obtained using observation and interview methods with 10 (ten) employees. The techniques used in collecting data in this research include observation and interviews. The data analysis technique goes through two stages, namely data codification, data presentation, and drawing conclusions. The research results show that the marketing strategy to increase customer buying interest implemented by Sun Cafe Gunungsitoli City has been implemented well through market segmentation, targeting and positioning approaches. However, all marketing strategies that have been implemented by Sun Cafe Gunungsitoli City still need to be improved in order to increase consumer buying interest and support a sustainable increase in sales